PENERAPAN HOSPITALITY TOURISM DI DESA WISATA PENGLIPURAN Ditinjau dari Attractions, Accesibilities, Amenities, Ancillaries, And Community Involvement - Putu Ratih Pertiwi (Jurnal Ilmiah Hospitality Management, 2013)
These days tourism has becoming a need, which stimulate many demands for travelling, tours, leisure, and increasing the tourism and hospitality business in every destination. There is no other reason for those paradigms, beside to fulfill the needs of tourism to support and facilitate the development of tourism. One of the important factors to meet the tourists’ needs is an accommodation or lodging. In This globalization era where we could see many intense competitions between every lodging business, one which could stay run in long-term period, is the one who is capable to satisfy the wants and the needs of their customers. The purpose of this research is to identify the hospitality implementation in one of the rural tourism destination in Bali: Penglipuran Traditional Village in terms of attraction, accessibilities, amenities, ancillaries, and community involvement.